2018
DOI: 10.1039/c8tx00102b
|View full text |Cite
|
Sign up to set email alerts
|

Maternal SSRIs experience and risk of ASD in offspring: a review

Abstract: Antidepressants are extensively used during pregnancy and associated with severe outcomes, including innate malformations, prematurity, and low birth weight, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…The data are highly congruent, however, with one proposed biological mechanism of ASD development, serotonin metabolism dysfunctions, and serotonergic changes (64,65). Along the described limitations in addressing indication bias, in utero SSRI exposure may potentially intervene with the end-point diagnosis as well (66). Mechanisms which impact adults' 5-HT can last after discontinuation of treatment, and can…”
Section: The Association Between Prenatal Ssris and Autism Spectrum Dmentioning
confidence: 87%
“…The data are highly congruent, however, with one proposed biological mechanism of ASD development, serotonin metabolism dysfunctions, and serotonergic changes (64,65). Along the described limitations in addressing indication bias, in utero SSRI exposure may potentially intervene with the end-point diagnosis as well (66). Mechanisms which impact adults' 5-HT can last after discontinuation of treatment, and can…”
Section: The Association Between Prenatal Ssris and Autism Spectrum Dmentioning
confidence: 87%
“…Perinatal exposure to SSRIs is reported to negatively affect the plasticity of developing hippocampus especially in male fetus, which affects children's behavioral development [31]. In accordance, a number of recent systematic reviews and meta-analyses report that antenatal use of antidepressants (SSRIs) increases the risk of attention-deficit/ hyperactivity disorder and autism spectrum disorders [7,[32][33][34].…”
Section: The Effect Of Gestational Exposure To Antidepressants On Growing Childrenmentioning
confidence: 97%
“…As a result of such a stressed fetal neurodevelopment, these children are at a great risk of delayed cognitive and motor development as well as impaired tolerance to stressful conditions [3,4]. In the same way, postnatal depression represents a risk for non-optimal parenting behaviors, impaired mother-child interactions, child victimization, and development of childhood psychopathology [5,6].Antidepressant medications-and in particular, selective serotonin reuptake inhibitors (SSRIs)-are considered as the first line of treatment of perinatal depression [7,8]. It is estimated that 10% of pregnant women are prescribed antidepressant medications [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fatima et al [111] recently assessed the data only of studies reporting on a positive association between prenatal SRI exposure and ASD. The authors concluded that there is some signal of a possible association, but their conclusion is weakened by the fact that they did not include any of the “negative” studies that did not report any association.…”
Section: Possible Association With Autism Spectrum Disorder (Asd)mentioning
confidence: 99%